Ukrainian museography on the waves of censorship fluctuations (late 19th – early 20th centuries) - Cherhik, Natalia (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2021)
Purpose of the research: to reveal the specifics of the subordination of Ukrainian museography to the legislation of the Russian Empire with reference to information policy and the press. Object of research: typographic designations, illustrations, texts of Ukrainian museographic works published in the Russian Empire in the late 19th – early 20th centuries. The subject of the research: the process of passing the censorship of museum publications of the specified geographical segment and historical period. Scientific novelty. The work for the first time comprehensively demonstrates the subordination of museographic publications of Ukrainian origin to the requirements of censorship legislation, which was in force in the Russian Empire during the late 19th – early 20th centuries. Research methodology. Procedural aspects of the passage of censorship have been established based on the analysis of the official apparatus of the books. The release of Ukrainian museographic works is presented in three chronological blocks against the background of the legislative process on freedom of the press. Taking into account that additional restrictive censorship rules were in force in the Ukrainian provinces of the Russian Empire (the so-called «Valuevsky circular» of 1863 and «Emsky decree» of 1876), the textual and illustrative components of the editions were analyzed. Relevance. The study of the process of overcoming legislative prohibitions on freedom of speech by Ukrainian museographers will make it possible in a qualitatively new way, through the prism of publishing, to assess the state and development of museums in Ukraine over the specified period.